The Prevalence of Undiagnosed Age-Related Sight-Threatening Diseases in Self-Proclaimed Healthy Individuals - Sophie Lemmens; João Barbosa Breda; Karel Van Keer; Tine Jacobs; Ruben Van Landeghem; Patrick De Boever; Ingeborg Stalmans (Journal of Ophthalmology)
Background. Age-related conditions such as glaucoma, age-related macular degeneration, diabetic retinopathy, and cataract have become the major cause of visual impairment and blindness in high-income countries. The aim of the current study is to investigate the prevalence of these eye diseases in a cohort of self-proclaimed healthy elderly and thus get a rough estimation of the prevalence of undiagnosed age-related eye conditions in the Belgian population. Methods. Individuals aged 55 and older without ophthalmological complaints were asked to fill in a general medical questionnaire and underwent an ophthalmological examination, which included a biomicroscopic examination, intraocular pressure measurement, axial length measurement, and acquisition of fundus pictures and optical coherence tomography scans. Information regarding follow-up was collected in those who received the advice of referral to an ophthalmologist or the advice to have more frequent follow-up visits, based on their study evaluation. Results. The cohort included 102 people and comprised 46% men (median age 70 years, range 57–85 years). Referral for additional examinations was made in 26 participants (25%). The advice to have more regular follow-up ophthalmologist visits was given to nine additional participants (9%). No significant correlations between baseline characteristics and the need for referral could be identified. Follow-up information was available for 25 out of 26 referred volunteers. Out of these, four underwent a therapeutic intervention based on study referral, up until 18 months after study participation. All four interventions took place in the age group 65–74 years. Conclusions. This study shows that, even in an elderly population with self-proclaimed healthy eyes and good general health, a significant proportion of subjects showed ocular findings that need regular follow-up and/or intervention. The frequency of prior ophthalmological examinations does not seem to be relevant to this proportion, meaning that everyone above 55 years old needs a routine ophthalmological evaluation.